Attitudes towards prenatal diagnosis and carrier screening for cystic fibrosis among the parents of patients in a paediatric cystic fibrosis clinic. - Watson, E K (1992)
The parents of all children attending the Royal Brompton National Heart and Lung Hospital cystic fibrosis paediatric clinic were asked to complete an anonymous postal questionnaire addressing attitudes towards prenatal diagnosis and population carrier screening for cystic fibrosis (CF); 65% (170/261) of parents responded. Of the respondents, 92% would support the introduction of a population screening test to detect carriers of CF and 19% felt such a test should be mandatory. A total of 64% of CF parents felt they would choose not to have any further children in the knowledge that they were both carriers, 74% would choose to have a prenatal test if they became pregnant, 44% would consider terminating an affected pregnancy, 33% would not, and 23% were unsure. Overall, 72% of respondents indicated they would choose to avoid having a further child with CF either by not having further children or by terminating an affected pregnancy.